The Current international context and it s macroeconomic repercussions for Latin america and the Caribbean (UN ECLAC SantiagoCL, 2013)
Identifies the key aspects of the current international economic situation and their principal implications for the macroeconomic performance of Latin America and the Caribbean.
Keywords: INTERNATIONAL ECONOMY